Fine Motor Occupational Therapy and Cognitive Outcomes in Children With Intellectual Disability: Terapi Okupasi Motorik Halus dan Hasil Kognitif pada Anak Tunagrahita - Nafaza, Firna Malinda Putri; Masithoh, Anny Rosiana; Rahmawati, Ashri Maulida (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Children with intellectual disability experience persistent limitations in cognitive development that affect learning, attention, and daily functioning, necessitating structured therapeutic approaches within special education settings. Specific Background: Fine motor occupational therapy activities, particularly cutting and pasting, are assumed to engage hand–eye coordination, concentration, and visual–motor integration relevant to cognitive processes in children with intellectual disability. Knowledge Gap: Empirical studies examining cutting and pasting as a fine motor occupational therapy intervention for cognitive outcomes in children with intellectual disability remain limited. Aims: This study aimed to examine cognitive changes following fine motor occupational therapy using cutting and pasting activities among children with intellectual disability in a special school context. Results: A quasi-experimental design with pre-test and post-test control groups involved 67 participants assessed using the Bender–Gestalt test. Significant cognitive improvement was observed in the intervention group (p = 0.000), while the control group showed no significant change (p = 0.083). Post-intervention comparison demonstrated a significant difference between groups (p = 0.002). Novelty: This study provides empirical evidence on the application of cutting and pasting as a fine motor occupational therapy approach specifically targeting cognitive functions in children with intellectual disability. Implications: The findings support the integration of cutting and pasting activities as structured occupational therapy and nursing interventions in special schools to support cognitive development and functional independence among children with special needs. Highlights • Fine motor occupational therapy activities showed measurable cognitive changes in children with intellectual disability• Cutting and pasting tasks differentiated cognitive outcomes between intervention and control groups• Structured occupational therapy supported learning processes in special school settings Keywords Fine Motor Occupational Therapy; Cognitive Function; Cutting And Pasting; Intellectual Disability; Special Education